Analisis Niat Mahasiswa Diploma III Akuntansi Menggunakan Google Classroom - Yanto Darmawan; Dwi Haryono Wiratno; Sururi Sururi; Hasan Subagyo (Akuntabilitas, 2022)
Google Classroom has become a popular e-learning management system in higher education during the covid-19 pandemic. However, successful implementation of Google Classroom requires acceptance by students. This study aims to explain the factors that influence accounting students’ intention to accept Google Classroom This study uses an Extended the Technology Acceptance Model to assess the acceptance and intention to use Google Classroom. Data was obtained from 326 students of Politeknik YKPN Yogyakarta through online questionnaire using Google Form. The Structural Equation Modelling – Partial Least Square approach is used to assess the measurement model and structural model. This study concludes that 1) perceived ease has no effect on students’ intention to use Google Classroom, 2) perceived of ease Google Classroom has a positive effect on perceived usefulness of Google Classroom, 3) perceived usefulness has a positive effect on students’ intention to use Google Classroom, 4) perceived behavioral control does not affect students’ intentions to use Google Classroom, and 5) subjective norms affect students’ intentions to use Google Classroom.